Epistemic Modality across the Use of Lexical Verbs in George W. Bush's Speeches - Alsbbagh, Yasir Ahmed Mohammed Ridha; Abdullah, Imran Ho; Muthmainnah, Muthmainnah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study employs a corpus linguistic approach, utilizing qualitative and quantitative concurrent mixed methods, to analyze epistemic modal lexical verbs (EMLVs) in George W. Bush's speeches. The dataset comprises six speeches delivered by the former president between September 11, 2001, and December 16, 2004, a period of significant importance in the Middle East, totaling 24,209 words with 308 instances of EMLVs. Software tools, including AntConc version 3.5.9 (last updated in December 2020), were utilized to extract modal expressions from these speeches. The research aims to elucidate how George W. Bush utilized EMLVs to persuade audiences. The study identifies nine primary functions of EMLVs in State of the Union speeches, encompassing Assertion, Assumption, Conviction, Recommendation, Anticipation, Tricky/Elusiveness, Desire, Hedging, and Contemplation. Conversely, War speeches exhibit eight functions, including Assertion, Hedging, Desire, Conviction, Likelihood/Possibility, Anticipation, Tricky/Elusiveness, and Prediction. The findings indicate that Assertion emerges as the most frequently employed function in both genres, highlighting the pivotal role of EMLVs in political discourse for motivating, advancing agendas, and garnering support for initiatives.